2017
DOI: 10.4103/jnrp.jnrp_387_16
|View full text |Cite
|
Sign up to set email alerts
|

Guillain–Barre Syndrome following Tuberculosis: A Rare Association

Abstract: The co-occurrence of Guillain–Barre syndrome (GBS) and tuberculosis is rare. Even in countries like India, where tuberculosis is common, there is only one case report of co-occurrence of GBS with tuberculosis. We report a case of GBS in association with sputum-positive pulmonary tuberculosis. The earliest treatment with intravenous immunoglobulin in acute motor axonal neuropathy variant of GBS would show good early recovery despite associated pulmonary tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The review of reported cases is mentioned in Table 1 . 3 4 5 6 8 9 10 The most common clinical features of the presentation of GBS are ascending quadriparesis with areflexia or hyporeflexia, and few case reports showed sensory involvement. 4 8…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The review of reported cases is mentioned in Table 1 . 3 4 5 6 8 9 10 The most common clinical features of the presentation of GBS are ascending quadriparesis with areflexia or hyporeflexia, and few case reports showed sensory involvement. 4 8…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of GBS in TB is best explained by molecular mimicry involving both cell-mediated and humoral immune responses. 3 The review of reported cases is mentioned in ►Table 1. [3][4][5][6][8][9][10] The most common clinical features of the presentation of GBS are ascending quadriparesis with areflexia or hyporeflexia, and few case reports showed sensory involvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Guillain–Barre syndrome (GBS) is an acute, monophasic, symmetrically progressive, peripheral ascending inflam-matory polyneuropathy characterized by limb weakness, areflexia, absent or mild sensory signs, and variable autonomic disturbances. 1 It is the most common cause of acute flaccid paralysis (AFP) worldwide after eradication of poliomyelitis, with an estimated incidence of 0.8 to 1.9 cases per 100,000 persons. Two-thirds of GBS cases are preceded by infections with bacteria such as Campylobacter jejuni, Mycoplasma pneumonia, and viruses such as dengue, chikungunya, CMV, Epstein–Barr virus, Zika, and human immunodeficiency virus (HIV) or vaccines and surgery.…”
Section: Introductionmentioning
confidence: 99%